Diagnosis and treatment of canine discoid lupus erythematosus: Case report - da silva, vanessa; Monteiro, Cynthia; Silva, Michelle; Carneiro, Raimundo; Lucena, Lorena (Pubvet, 2018)
The Lupus Erythematosus immune complex disease (LE) consists of a set of autoimmune dermatopathies that can manifest in two main clinical presentations: Systemic Lupus Erythematosus (SLE) and Discoid Lupus Erythematosus (DLE). The clinical diagnosis of DLE can be challenging, due to the variety of symptoms that can occur both in lupus and in other dermatological conditions, which interferes with the early diagnosis and consequently a delay in the treatment and improvement of the patient. This study aims to report the importance of histopathological examination in the definitive diagnosis for treatment and favorable prognosis of canine poodle with DLE. A poodle dog was attended at the Metropolitan Veterinary Polyclinic - HVM, presenting lesion in nasal area with previous treatments and no apparent improvment of the lesion. Laboratory and cytological exams were done to exclude other skin diseases. After an inconclusive result in the cytology, the histopathological examination was requested, to define the exact diagnosis and exclusion of other dermatopathies. The histopathological confirmed the diagnosis of Discoid Lupus Erythematosus. Treatment with corticosteroids at the dose of 1.0mg / kg, antioxidant vitamins and sunscreen was instituted. After 10 days, the dose increased to 2.5mg / kg, which is the immunosuppressive dose. The animal presented a response with a decrease in the crustal region of the lesion in the nasal plane.